Simultaneous removal of lead(II), chromium(III), and copper(II) heavy metal ions through an adsorption process using C-phenylcalix[4]pyrogallolarene material. Issue 4 (August 2020) - Jumina,; Priastomo, Yoga; Setiawan, Hamid Rohma; Mutmainah,; Kurniawan, Yehezkiel Steven; Ohto, Keisuke
Highlights: C -phenylcalix[4]pyrogallolarene, is a good adsorbent material for lead(II), chromium(III), and copper(II) ions. The kinetic of lead(II), chromium(III), copper(II), and nickel(II) ions adsorption follows pseudo-second order reaction. The adsorption of lead(II), chromium(III), copper(II), and nickel(II) ions fits well with the Langmuir model. Ion exchange is the main mechanism occurring in the heavy metal adsorption onto C-phenylcalix[4]pyrogallolarene material. Abstract: Heavy metal ion removal remains a serious challenge to the sustainability of our environment. In this work, a simple adsorbent, i.e., C -phenylcalix[4]pyrogallolarene bearing 12 phenolic functional groups, has been successfully synthesized and evaluated for the simultaneous adsorption of heavy metal ions in acidic media. Results showed that C -phenylcalix[4]pyrogallolarene exhibited good adsorption percentages for heavy metal ions, i.e., lead(II), chromium(III), copper(II), and nickel(II). Given that the adsorption of all metal ions was driven by the ion exchange mechanism, the adsorption process depends on the pH value of the aqueous phase, yielding the optimum pH values of 5.0, 4.9, 5.2, and 7.9 for lead(II), chromium(III), copper(II), and nickel(II) ions, respectively. The kinetics of heavy metal ion adsorption was governed by the pseudo-second order model, whereas the adsorption isotherm behavior was governed by the Langmuir model. The results also showed that the adsorption capacities for lead(II), chromium(III), copper(II), and nickel(II) were 60.97, 14.31, 8.14, and 16.86 mg g −1, respectively. The interaction between heavy metal ions and C -phenylcalix[4]pyrogallolarene was also investigated through UV–vis, FTIR, and 1 H-nuclear magnetic resonance (NMR) spectroscopic studies. The findings showed that C -phenylcalix[4]pyrogallolarene is a potential adsorbent material for the simultaneous removal of heavy metal ions.